Bodily Vulnerability and the Ethics of Representing Woman and Nation in the Poetry of Eavan Boland - Clutterbuck, Caitriona (ABEI Journal, 2021)
This essay argues that for Eavan Boland, all genuinely life-enhancing social, cultural and political engagement depends on our capacity to respond to the exposed and vulnerable condition of the human body in time. In the Irish context, such alertness to the historically-situated suffering body has a particular bearing on the ethics of representation in art. Boland’s output diagnoses the legacy of colonialism as authorizing a dangerous three-way intersection between the heroization of territorial and racial violence, the normalization of gender and class injustice, and the sanctioning of an exclusivist aesthetics in the poetry tradition—all three of these outcomes demanding denial of our common fate of mortality. For Boland, this toxically-clamped nexus can only be released through focusing on corporeal vulnerability as a primary human condition: one which binds the marginalized first and foremost to each other but also to those who perpetrate or perpetuate their exclusion. For Boland, openness to the flux of change leading towards bodily dissolution is particularly crucial for understanding the vexed relationship between woman and nation in Irish culture, and to renewing that relationship on creative terms.